The iron princess - Hambly, Barbara (Open Road Integrated Media, Inc., 2023)
"Something is amiss with the world's magic. Spells don't work the way they used to--when they work at all. Only the powers of the Crystal Mages remain as they were, powers founded on the use of the mystical element adamis, the harvesting of which has enslaved the peoples of the Twilight Lands. They need a hero. At the same time, ravenous beasts have begun to appear, legendary creatures that seem to be proof against any magic. And Clea Stylachos, granddaughter of a great sage of the Twilight people, has reason to fear that the Crystal Mages, instead of seeking to defeat these insanely destructive monsters, are attempting to weaponize them in their quest for power. Clea's only hope to save her people is a wizard who retains his power, one who will not betray her, either to the great merchant houses or to the all-entangling web of the Crystal Mages. But that wizard--Ithrazel the Cursed--wants nothing to do with saving the world, helping a hero, or unraveling the terrible secret at the heart of the Crystal Mages' plans"